TEKNIK MULSA VERTIKAL PADA BUDIDAYA TEBU (Saccharum officinarum.L) RATOON SATU - Abusari Marbun; Abdul Rauf; Hanum Hanum (Jurnal Pertanian Tropik, 2016)
Sugarcane (Saccharum officinarum.L) is the main material in sugar industry. An effort to improve the quality of dry land for sugarcane cultivation is important. One of the effort than can be done is the additional of organic metter to the soil. The objective of this research was to determine the effect of vertical mulching techniques for soil organic matter content and soil chemistry fertility and its relationship with the vegetative growth of the ratoon sugarcane. This research was conducted at Agricultural High School Practice (STPP) Medan-Binjai KM.10 districts Sunggal Deli Serdang, North Sumatra, from May -December 2013. This study was conducted using a randomized block design non factorial with four treatments, were: horizontal mulch (M1), vertical mulch (M2), vertical mulch with Trichoderma sp. (M3), Vertical mulch mixed with cow manure (M4). The result from the research showed, that vertical mulch mixture with manure can increase the level of C-organic, N-content, and the lower of Ratio C/ N . Vertical mulching treatment mix with manure, increasing the shoot length of sugarcane 21.9%, the number of plants per clump 6.8%, the number of plants per meter 50%, wet weight 68.28% and dry weight 41.9%, compared with horizontal mulch